The impact of democracy and income on CO2 emissions in MINT countries: evidence from quantile regression model - Abdul Agbede, Esther; Bani, Yasmin; Mohd Naseem, Niaz Ahmad; Wan Azman-Saini, Wan Ngah (Springer Nature, 2023)
This study analyses the relationship between democracy and environmental pollution in the MINT countries using a panel data spanning 1971“2016. It also investigates the interactive efect of income and democracy on CO2 emissions. We used various estimation techniques for the analysis, ranging from the quantile regression, OLS-fxed efect and GLS-random efect regressions with Driscoll-Kraay standard errors to control for cross-sectional dependence while a panel threshold regression is used for robustness check. The results showed existence of long-run relationship between CO2 emissions and the explanatory variables. The quantile regression results for interaction model indicate that economic growth, democracy and trade openness promote environmental pollution via their positive efects on CO2 emissions. Primary energy however reduces pollution across the lower and middle quantiles but enhances it in higher quantiles. The interaction efect is negative and statistically signifcant across all quantiles. This implies that democracy has a signifcant role in moderating the impact of income on CO2 emission in the MINT countries. It thus follows that if the MINT countries radically strengthen democracy and enhance income, it would be possible for them to achieve greater economic development and reduce CO2. In addition, a single threshold model is used to identify the asymmetry in response to CO2 emissions at lower and upper levels of democratic regimes. The results showed that once the degree of democracy is above the threshold level, an increase in income would reduce CO2 emissions but once it is below the threshold level, the efect of income becomes insignifcant. Based on these results, the MINT countries need to strengthen democracy, enhance income level and relax trade barriers.